A Score Test for Box-Cox Functional Form - YANG, Zhenlin (Institutional Knowledge at Singapore Management University, 2003)
This paper presents two score tests to determine a value for the Box-Cox transformation parameter. The test based on expected information performs better in small samples and is computationally simpler than the one based on observed information; therefore, the former is recommended.